(untitled) (Research, Society and Development, 2022)
The present study aims to identify the probable gestational risk factors for the development of Autism Spectrum Disorder (ASD). The study is of the quantitative, descriptive, documentary type, with an exploratory analysis of the data. Secondary data from 32 medical records of children diagnosed with classical autism were used. Regarding the age of the parents at conception, the highest percentage of mothers was between 20 and 30 years old (56.25%) and of parents between 32 and 45 years old (59.38%). Urinary Tract Infections (UTI) were the most common infections during pregnancy (43.80%). Regarding to the other prenatal clinical intercurrences, different types of intercurrences predominated (40.63%), followed by metabolic disorders (25.00%). For the peri- and postnatal intercurrences, the majority were defined as different types (43.75%), followed by prematurity (28.13%). Considering the drugs used in pregnancy, most of the mothers used different types of medications (56.25%), followed by antibiotics (50.00%). Thus, to know the probable environmental factors involved in the etiology of ASD, enabling professionals to identify the most susceptible pregnant women and opportune intervention strategies in the prenatal care.